Study of Glass Tilt Angle to Achieve Optimum Overall Thermal Transfer Value (OTTV) - Wiyugo Hari Pranoto; Jatmika Adi Suryabrata; Moch Santosa (Departement of Architecture, Universitas Islam Indonesia, 2019)
Glass Reflectance is the ability of the glass surface to reflect light when passing through the glass surface. All types of glass have this capability (Clear Glass, Tinted Glass, and Reflective Glass). With its ability, not all the light will be passed through the glass because the glass surface will reflect some of the light. The magnitude of reflection depends on the tilt angle of the glass against the light direction. It means if the glass is applied to the building façade and exposed to sunlight, not all sunlight and the heat forwarded into the building. To know the exact tilt angle of the glass when applied to the building, research on the effectiveness of light reflection by the tilt angle of the glass is necessary. This research uses a computer simulation method with hypothetical building objects. This research aims to test how effective the tilt angle of glass reflects the sunlight when applied as the building facade. The tilt angle tested in the simulation is a tilted and rotated glass. The tilt angle effect of the glass can be calculated using the building’s OTTV (Overall Thermal Transfer Value).Keywords: tilt angle glass, OTTV, simulation